Elements of Article Law Number 1 of 2023 concerning the Criminal Code - Yusep Mulyana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
It is considered that Law Number 1 of 2023 concerning the Criminal Code still contains articles inherited from colonialism and is prone to being used as a means of criminalization. For example, the contents of the article on treason. Article 192 of the new Criminal Code states that anyone who commits treason with the intention that part or all of the territory of the Unitary Republic of Indonesia falls to foreign powers or to separate themselves from the Unitary State of the Republic of Indonesia shall be punished with death penalty, life imprisonment, or a maximum imprisonment of 20 years. Article 193 paragraph (1) stipulates that anyone who commits treason with the intention of overthrowing the government, shall be punished with a maximum imprisonment of 12 years. Meanwhile, Article 193 paragraph (2) states that leaders or organizers of treason are subject to imprisonment for a maximum of 15 years. Elements of Article Law Number 1 of 2023 Concerning the Criminal Code To find out whether an act in a legal event is a crime, an analysis can be carried out regarding whether the act has fulfilled the elements regulated in a particular criminal law article. For this reason, adjustments or matches (parts/events) of the incident must be made to the elements of the offense being charged. If it turns out to be suitable, then it can be determined that the incident is a criminal act that has occurred for which (can) be held criminally responsible to the perpetrator subject.